English Learning Style for Young Learners through Collaborative Learning at SD Negeri 5 Palembang - Agustiawati, Hartini; Orenza, Della Teresia (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2024)
English is a tool for communication. The use of English will be challenging Nowadays. In this study, the collaborative learning has been used to improve students’ motivation in learning English. The descriptive method was used in this study. The observation, interview and students’ answer were the instrument test of this study. The result showed that there was improvement in students’ achievement in learning English after the use of collaborative learning. This concludes that, it was approved that the use of collaborative learning improved and significantly gave high contribution to the students’ achievement.